Estimation of gas production and post-ruminal crude protein from native or ensiled Pisum sativum and Vicia faba grains. Issue 1 (1st January 2020) - Bachmann, M.; Kuhnitzsch, C.; Martens, S.D.; Steinhöfel, O.; Zeyner, A.
ABSTRACT: Gas production and post-ruminal crude protein (PRCP) were measured in vitro using the modified Hohenheim Gas Test (HGT) and the ANKOM RF Gas Production System (AGPS). Ruminal fluid was collected from cannulated wethers. The microbial inoculum was prepared according to the HGT and incubated with both in vitro systems. Total gases accumulated after 8 or 24 h were manually read off (modified HGT) and cumulative gas pressures were automatically recorded (AGPS). Determined NH3 -N concentrations were used to estimate PRCP. Peas had a greater gas production capacity than field beans ( P < 0.05). The ranking of 24 h-gas production from the substrates was equal with both systems ( R 2 = 0.57). The field beans had more PRCP than the peas, and PRCP differed between the systems ( P < 0.05). Current ensiling conditions had no effect on gas production. Ensiling did not affect PRCP concentrations in peas, but reduced them in the field beans ( P > 0.05 with the modified HGT; P < 0.05 with AGPS). Using the AGPS, PRCP was clearer differentiated among the substrates and had a clearer progression along increasing assumed ruminal passage rates. This indicates a better sensitivity of the AGPS compared to the modified HGT.